THEORETICAL FUNDAMENTALS OF EFFICIENCYOF AGRICULTURAL ENTERPRISES - BAHAN, NADIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers theoretical updates on the efficiency of resource use of agricultural enterprises. Researchers' views on the essence of the concept of "resources" and their own statement of the concept of "resources of the agricultural enterprise", which is a set of interconnected natural, tangible, intangible, financial, labor, time and information factors that interact with each other and taking into account the influence of external and internal environmental factors ensure the smooth operation of the agricultural enterprise in order to obtain maximum profits, taking into account the economic, environmental and social bases.The classification of types of resources of the agricultural enterprises which structure includes material (includes raw materials, materials) is offered; intangible (including licenses, innovative technologies), labor (able-bodied population), financial (include equity and borrowed capital, cash), natural (natural forces and substances), energy (include power of mechanical engines), information (documents and document arrays) and time (ability to make quick decisions) resources. This classification is proposed in order to take into account the characteristics and distinctive characteristics of the types of resources of agricultural enterprises, and at the same time, in order not to overload the more detailed division of resources.A study of the types of resource efficiency allocated by domestic and foreign scientists has been conducted. Scholars' views on the types of efficiency differ significantly, in particular, fourteen types of resource efficiency have been identified. Taking into account their diversity and peculiarities of typification, it is proposed to further conduct research on economic, environmental and social efficiency of the use of resources of agricultural enterprises.
Keywords: agricultural enterprise; resource; economic efficiency; social efficiency; environmental efficiency